Peningkatan Minat Baca Anak melalui Program Sehari Bersama Seleb (Selembar Buku) di Desa Jonggol Jambon Ponorogo - Sendyta Meilani; Mughniatul Ilma (Jurusan Ilmu Pendidikan Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2021)
This research activity is based on the low and lack of interest in reading the children of Jonggol Village, Jambon District, Ponorogo Regency. This can be seen from the results of observations that have been made by researchers by looking at the condition of the children of Jonggol Village and through interviews with one of the parents of the children of Jonggol Village. The purpose of this research is to raise awareness of students' interest in reading to the culture of reading literacy in elementary school age children in Jonggol Village, Jambon District, Ponorogo Regency. This Celebrity Day Work Program (a book) uses an approach in the form of the ABCD (Asset Bcased Community Development) research method. The use of this method is to empower the community with the potential that already exists in the assisted partners. The priority of this research is the growth of reading interest in the children of Jonggol Village, Jambon District, Ponorogo Regency. The results of the One Day Together Celebrity program are showing a significant change in the children of Jonggol Village.